Micropropagation of Camptotheca Acuminata Decne (Nyssaceae) – Endangered Ornamental and Medicinal Tree - Lilyana Nacheva; Nataliya Dimitrova; Valeria Ivanova; Fuliang Cao; Zunling Zhu (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2020)
Camptotheca acuminata Decne (Nyssaceae) (happy tree, tree of life, cancer tree) is a rapidly growing deciduous and endangered tree endemic to east Tibet and southern China (Liu et al., 2002). C. acuminata is an ornamental tree with monopodial growth, beautiful leaves and shade- and cold- tolerant in their natural environment. Recently, its demand has grown rapidly due to secondary metabolites production like Camptothecin and its derivatives with anti cancer and antivirus activity. The aim of the present study was to develop an efficient protocol for in vitro micropropagation of this valuable plant. Different cultural media based on both MS (Murashige and Skoog, 1962) or DKW (Driver and Kuniyuki, 1984) formulations with different cytokinins (6-benzylaminopurine, BAP or 2-isopentenyladenine, 2iP or meta-topolin, mT) have been involved. The aromatic cytokinin meta-topolin stimulated plant growth. The optimum multiplication rate of Camptotheca shoots occurred on the DKW basal medium, supplemented with 2.5 µM meta-topolin, grown under mixed LED light. The highest number of roots per plantlets was recorded on the rooting medium with 0.3 mgl-1 NAA.